De l'Estudi General a la Universitat de les Illes Balears. - JUAN VIDAL, JOSEP (Scripta, 2020)
The Estudi General de la Ciutat de Mallorca was an institution founded in Palma in 1483 which awarded degrees in theology, philosophy and the arts, valid only in the kingdoms of the Spanish monarchy. From the mid 16th century, it faced competition from a Jesuit college. To win this battle, it asked the Pope to recognize the validity of its qualifications throughout the whole of the Christian world, and this request was granted in 1673. Due to financial difficulties, the university-known as the Universitat Lul·liana de Mallorca or Lullian University of Mallorca-did not start operating until 1691 and, in 1772, its name was changed to the Universitat Literària de Mallorca (Mallorca Literary University). The institution was abolished in 1842 and no university studies were available in Mallorca until 1967, with the ensuing creation of the Universitat de les Illes Balears (University of the Balearic Islands) in 1978.